Tensile Strength Evaluation of MIG-Welded AISI 1045 Carbon Steel with Post Weld Heat Treatment - Muhammad Arsyad; Yusuf Rizal Fauzi (Asian Journal of Mechanical Engineering, 2025)
This study aims to investigate the effect of Post Weld Heat Treatment (PWHT) on the tensile strength of similar material welding. An experimental method was used in this research. The samples consisted of AISI 1045 carbon steel welded using the Metal Inert Gas (MIG) method, followed by PWHT. The MIG welding process was performed with varying current levels of 80 A, 90 A, and 100 A. PWHT was applied at different temperatures: 600°C, 700°C, and 800°C. Data were analyzed using quantitative descriptive methods based on tensile test results. The findings show that: (1) The PWHT at 600°C resulted in the highest tensile strength of 893.33 MPa, outperforming treatments at 800°C (680.88 MPa) and 700°C, as well as the non-PWHT sample (658.66 MPa). (2) PWHT temperature significantly influences tensile strength. (3) The optimal welding condition was found at a current of 100 A combined with a PWHT temperature of 600°C, yielding the highest tensile strength in AISI 1045 material.